2013
DOI: 10.1055/s-0033-1344714
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of in vivo identification of pancreatic cystic neoplasms with needle-based confocal laser endomicroscopy under endosonographic guidance

Abstract: These preliminary data suggested that nCLE has a high specificity in the detection of PCN, but may be limited by a low sensitivity. The safety of nCLE requires further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
151
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(161 citation statements)
references
References 9 publications
5
151
0
5
Order By: Relevance
“…They found that the presence of epithelial villous structures correlated with pancreatic cystic neoplasms with a specificity of 100%, but a low sensitivity of 59% (P = 0.004). 31,43 The complication rate was 9%, including two cases of pancreatitis and three with intracystic bleeding. 43 Napoléon et al 44 implemented a pilot study to ascertain diagnostic criteria for serous cystadenomas using nCLE imaging in 31 patients with single pancreatic cystic lesions.…”
Section: Confocal Laser Endomicroscopymentioning
confidence: 97%
See 3 more Smart Citations
“…They found that the presence of epithelial villous structures correlated with pancreatic cystic neoplasms with a specificity of 100%, but a low sensitivity of 59% (P = 0.004). 31,43 The complication rate was 9%, including two cases of pancreatitis and three with intracystic bleeding. 43 Napoléon et al 44 implemented a pilot study to ascertain diagnostic criteria for serous cystadenomas using nCLE imaging in 31 patients with single pancreatic cystic lesions.…”
Section: Confocal Laser Endomicroscopymentioning
confidence: 97%
“…31,43 The complication rate was 9%, including two cases of pancreatitis and three with intracystic bleeding. 43 Napoléon et al 44 implemented a pilot study to ascertain diagnostic criteria for serous cystadenomas using nCLE imaging in 31 patients with single pancreatic cystic lesions. Their study demonstrated data similar to Konda and colleagues with a specificity of 100% and sensitivity of 69% for the presence of superficial vascular network pattern.…”
Section: Confocal Laser Endomicroscopymentioning
confidence: 97%
See 2 more Smart Citations
“…The proximal scanning method is used in the Cellvizio system (Mauna Kea Technologies, France) and several variations of this system are now available [46][47][48] , with the thinnest probe offered by Mauna Kea Technologies having an outer diameter of 0.85 mm (REF. 49). Simple non-scanning endomicroscopes, using a fibre-bundle to flood illuminate the sample and then collect images, have also been applied to the gastrointestinal tract 50,51 but not commercialized.…”
Section: Microbiota Changesmentioning
confidence: 99%